Furmonertinib for EGFR-mutant advanced non-small cell lung cancer: a glittering diamond in the rough of EGFR-TKI - Ding, Jianghua; Ding, Xingjing; Zeng, Jiao; Liu, Xiaoqun (Frontiers in Pharmacology, 2024)
The third-generation EGFR-TKIs, such as osimertinib, aumolertinib, and furmonertinib, have been recommended as the preferred treatment for EGFR-mutant advanced non-small cell lung cancer (NSCLC). Among them, furmonertinib shows several advantages in terms of clinical efficacy. Firstly, compared to osimertinib and aumolertinib, furmonertinib was the first EGFR-TKI with median progression-free survival (mPFS) of over 20.0m (20.8m) for advanced NSCLC with classical EGFRmutations. Furthermore, furmonertinib achieved a mPFS of 18.1m in advanced NSCLC with unfavorable prognostic factors, such as the 21 L858R mutation and central nervous system (CNS) metastasis, which is unrivalled by osimertinib. Secondly, Furmonertinib is the only FDA-approved EGFR-TKI for breakthrough therapy in newly-diagnosed advanced NSCLC with EGFR ex20ins mutation. Thirdly, the relatively longer mPFS of 20.8m was observed in furmonertinib compared to osimertinib and aumolertinib (15.2m and 15.3m) in EGFR-mutant advanced NSCLC with CNS metastases. More importantly, the efficacy of furmonertinib increases within the dose range of 80-240mg per day. Finally, furmonertinib can be an optional treatment for advanced NSCLC patients who develop resistance to osimertinib or aumolertinib. In conclusion, furmonertinib may be a glittering star in the field of EGFR-TKI, which requires further exploration and expansion.